ANALISIS KINERJA SIMPANG BERSINYAL (Studi Kasus Jalan Teuku Umar Barat – Jalan Gunung Salak) - Jaya Wikrama, A.A.N.A. (Jurnal Ilmiah Teknik Sipil; Vol. 15, No. 1 Januari 2011, 2012)
Intersection between Western Teuku Umar and Gunung Salak Roads which is located in Western Denpasar District has a high traffic volume. This intersection functions as a gateway connecting Denpasar City and Badung Region. The problems of the intersection are long delay and frequent accident. The objectives of this study are to evaluate the existing intersection performance and to analyze several alternative solutions. There were 3 alternatives improvement applied, i.e. First, signal re-setting with multi program; Second, combination of geometric re-design and signal re-setting and Third, combination of signal resetting and south traffic flow diversion. Delay was used as the intersection performance indicator. It was found that the second alternative as the best solution.
Keywords: delay, performance